New syllabus primary mathematics workbook 3A - Yee, Dr. Foong Pui (Karachi Oxford university Press., 2024)
New Syllabus Primary Mathematics Workbook 3A is designed to complement the Primary Mathematics 3 textbook by providing additional practice to reinforce the key mathematical concepts taught in the classroom. Covering topics such as numbers, addition, subtraction, multiplication, and division, the workbook features a variety of exercises to help students strengthen their understanding and improve problem-solving skills. The activities are designed to encourage independent learning and critical thinking, offering students opportunities to apply concepts in real-world scenarios. This workbook serves as an essential resource for building a strong mathematical foundation in preparation for more advanced topics.